Correlation analysis between the changes in plasma ghrelin level and weight loss after sleeve gastrectomy combined with fundoplication - Xin Li; Aikebaier Aili; Aliyeguli Aipire; Pierdiwasi Maimaitiyusupu; Maimaitiaili Maimaitiming; Kelimu Abudureyimu (BMC Surgery, 2024)
Abstract Background Laparoscopic sleeve gastrectomy combined with fundoplication (LSGFD) can significantly control body weight and achieve effective anti-reflux effects. The aim of this study is to investigate the correlation between the alteration in Ghrelin levels and weight loss following SGFD, and to compare Ghrelin levels, weight loss and metabolic improvements between SG and SGFD, with the objective of contributing to the existing body of knowledge on SGFD technique in the management of patients with obesity and gastroesophageal reflux disease (GERD). Methods A retrospective analysis was conducted on the clinical data of 115 obese patients who underwent bariatric surgery between March 2023 and June 2023 at the Department of Minimally Invasivew Surgery, Hernia and Abdominal Wall Surgery, People’s Hospital of Xinjiang Uygur Autonomous Region. The subjects were divided into two groups based on surgical methods: sleeve gastrectomy group (SG group, 93 cases) and sleeve gastrectomy combined with fundoplication group (SGFD group, 22 cases). Clinical data, such as ghrelin levels before and after the operation, were compared between the two groups, and the correlation between changes in ghrelin levels and weight loss effectiveness after the operation was analyzed. Results: Three months after the operation, there was no significant difference in body mass, BMI, EWL%, fasting blood glucose, triglyceride, cholesterol, and uric acid levels between the SG and SGFD groups (P > 0.05). However, the SGFD group exhibited a significant decrease in body weight, BMI, and uric acid levels compared to preoperative levels (P < 0.05), while the decrease in ghrelin levels was not statistically significant (P > 0.05). Logistic regression analysis indicated that ghrelin levels three months after the operation were influential in postoperative weight loss. Conclusion The reduction of plasma Ghrelin level in patients after SGFD is not as obvious as that in patients after SG, but it can make obese patients get the same good weight loss and metabolic improvement as patients after SG. Ghrelin level at the third month after operation is the influencing factor of postoperative weight loss.